Modelling the maternal-fetal interface: An in vitro approach to investigate nutrient and drug transport across the human placenta - Fuenzalida, Barbara; Basler, Virginia; Koechli, Nadja; Yi, Nan; Staud, Frantisek; Albrecht, Christiane (Journal of cellular and molecular medicine, 2024)
The placenta plays a critical role in maternal-fetal nutrient transport and fetal protection against drugs. Creating physiological in vitro models to study these processes is crucial, but technically challenging. This study introduces an efficient cell model that mimics the human placental barrier using co-cultures of primary trophoblasts and primary human umbilical vein endothelial cells (HUVEC) on a Transwell®-based system. Monolayer formation was examined over 7 days by determining transepithelial electrical resistance (TEER), permeability of Lucifer yellow (LY) and inulin, localization of transport proteins at the trophoblast membrane (immunofluorescence), and syncytialization markers (RT-qPCR/ELISA). We analysed diffusion-based (caffeine/antipyrine) and transport-based (leucine/Rhodamine-123) processes to study the transfer of physiologically relevant compounds. The latter relies on the adequate localization and function of the amino-acid transporter LAT1 and the drug transporter P-glycoprotein (P-gp) which were studied by immunofluorescence microscopy and application of respective inhibitors (2-Amino-2-norbornanecarboxylic acid (BCH) for LAT1; cyclosporine-A for P-gp). The formation of functional monolayer(s) was confirmed by increasing TEER values, low LY transfer rates, minimal inulin leakage, and appropriate expression/release of syncytialization markers. These results were supported by microscopic monitoring of monolayer formation. LAT1 was identified on the apical and basal sides of the trophoblast monolayer, while P-gp was apically localized. Transport assays confirmed the inhibition of LAT1 by BCH, reducing both intracellular leucine levels and leucine transport to the basal compartment. Inhibiting P-gp with cyclosporine-A increased intracellular Rhodamine-123 concentrations. Our in vitro model mimics key aspects of the human placental barrier. It represents a powerful tool to study nutrient and drug transport mechanisms across the placenta, assisting in evaluating safer pregnancy therapies.
Keywords: kokultivační techniky; Isoquinolines; biologické modely; biologický transport; Inulin; Female; Human Umbilical Vein Endothelial Cells; Rhodamine 123; ženské pohlaví; rhodamin 123; Placenta; lidé; Models, Biological; P-glykoprotein; těhotenství; ATP Binding Cassette Transporter, Subfamily B, Member 1; Trophoblasts; isochinoliny; Biological Transport; Leucine; maternofetální výměna látek; inulin; leucin; Maternal-Fetal Exchange; Coculture Techniques; endoteliální buňky pupečníkové žíly (lidské); Pregnancy; placenta; trofoblasty; Humans